Bolstering the Evidence Base for Integrating Abortion and HIV Care: A Literature Review - Ruth Manski; Amanda Dennis; Kelly Blanchard; Naomi Lince; Dan Grossman (AIDS Research and Treatment)
HIV-positive women have abortions at similar rates to their HIV-negative counterparts, yet little is known about clinical outcomes of abortion for HIV-positive women or the best practices for abortion provision. To fill that gap, we conducted a literature review of clinical outcomes of surgical and medication abortion among HIV-positive women. We identified three studies on clinical outcomes of surgical abortion among HIV-positive women; none showed significant differences in infectious complications by HIV status. A review of seven articles on similar gynecological procedures found no differences in complications by HIV status. No studies evaluated medication abortion among HIV-positive women. However, we did find that previously expressed concerns regarding blood loss and vomiting related to medication abortion for HIV-positive women are unwarranted based on our review of data showing that significant blood loss and vomiting are rare and short lived among women. We conclude that although there is limited research that addresses clinical outcomes of abortion for HIV-positive women, existing data suggest that medication and surgical abortion are safe and appropriate. Sexual and reproductive health and HIV integration efforts must include both options to prevent maternal mortality and morbidity and to ensure that HIV-positive women and women at risk of HIV can make informed reproductive decisions.